Photodynamically tunable ROS-generating hydrogels for accelerated tissue regeneration - Seung Hee Hong; Ye Jin Park; Seo In Lee; Ki Chang Nam; Mi Hee Lee; Jong-Chul Park (Bioactive Materials)
Wound healing progresses through many key cellular activities, including fibroblast and keratinocyte proliferation and angiogenesis. This study explored the wound-healing potential of reactive oxygen species (ROS)-generating hyaluronic acid (HA) hydrogels. We fabricated a chlorin e6–conjugated HA (Ce6-HA) hydrogel that generates ROS when subjected to irradiation from an LED light source. In vitro studies revealed that the ROS generated by the Ce6-HA hydrogels enhanced the proliferation of fibroblasts and keratinocytes. Further, the fibroblasts were found to have high levels of intracellular ROS, elevated expression of p-ERK1/2, p-p38 MAPK, p-Akt, and cyclin D1 proteins, and enhanced collagen deposition. Moreover, the Ce6-HA hydrogel also promoted endothelial angiogenesis in vitro. In vivo studies demonstrated the ROS-generating HA hydrogels significantly improved wound closure and tissue regeneration compared to control groups. The Ce6-HA hydrogel-treated group exhibited accelerated wound healing, with enhanced fibroblast proliferation, increased keratinocyte proliferation, and better angiogenesis. Histopathological and immunohistochemical analyses showed elevated levels of key growth factors and signaling molecules, which are critical to wound healing. The controlled ROS generation from the Ce6-HA hydrogels activated broader molecular pathways necessary for effective skin tissue repair. Therefore, ROS-triggering HA hydrogels could be a viable approach to accelerate recovery and reduce scarring in clinical settings.